Childhood Adversity and Associated Psychosocial Function in Adolescents with Complex Trauma - Beal, Sarah J. (Child Youth Care Forum, 2018)
BACKGROUND: Childhood adversity is linked to a number of adult health and psychosocial outcomes; however, it is not clear how to best assess and model childhood adversity reported by adolescents with known maltreatment exposure. OBJECTIVE: This study sought to identify an empirically-supported measurement model of childhood adversity for adolescents in child protective custody and associations among childhood adversity and adolescent outcomes. METHODS: Self-report survey data assessed childhood adversity and adolescent outcomes, including psychological wellbeing, quality of life, and substance use, in 151 adolescents ages 16 to 22 in protective custody with a documented maltreatment history. RESULTS: Findings suggest that, among youth with complex trauma histories, it is important to distinguish among risk related to unexpected tragedy (e.g., natural disaster, parental divorce), family instability (e.g., parental substance abuse or mental health concerns), and family violence (e.g., physical or sexual abuse). Family violence was associated with poorer psychological wellbeing and quality of life, while family instability was associated with cigarette and marijuana use. CONCLUSIONS: Among adolescents with complex trauma histories, childhood adversity assessments reflect multiple domains of adversity, each of which are differentially related to adolescent risks. Properly assessing childhood adversity in adolescents with complex trauma histories may help target interventions for specific risks (e.g., substance use) based on which types of childhood adversity youth have been exposed to.